2022
DOI: 10.3389/fmolb.2022.895814
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Molecular Targets to Relieve Endocrine-Related Diseases

Abstract: Transient receptor potential (TRP) channels are polymodal channels capable of sensing environmental stimuli, which are widely expressed on the plasma membrane of cells and play an essential role in the physiological or pathological processes of cells as sensors. TRPs often form functional homo- or heterotetramers that act as cation channels to flow Na+ and Ca2+, change membrane potential and [Ca2+]i (cytosolic [Ca2+]), and change protein expression levels, channel attributes, and regulatory factors. Under norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 242 publications
(346 reference statements)
0
5
0
Order By: Relevance
“…Both are regulated by PIP2 but differ in their high sensitivity to Ca2+. 92 TRPM4, identified as a homolog of MLSN (TRPM1), is highly expressed in the colon, prostate, kidney, and heart. 93 The c-terminal CaM binding site of TRPM4 is critical for susceptibility to Ca2±dependent activation.…”
Section: Activation Mechanisms Of the Trpm Channelsmentioning
confidence: 99%
“…Both are regulated by PIP2 but differ in their high sensitivity to Ca2+. 92 TRPM4, identified as a homolog of MLSN (TRPM1), is highly expressed in the colon, prostate, kidney, and heart. 93 The c-terminal CaM binding site of TRPM4 is critical for susceptibility to Ca2±dependent activation.…”
Section: Activation Mechanisms Of the Trpm Channelsmentioning
confidence: 99%
“…TRP channels are expressed in various tissues, including the skeletal muscle, pancreas, liver, kidney, vascular endothelium, adipose tissue, and others. They have been linked to metabolic diseases such as obesity, diabetes, dyslipidemia, atherosclerosis, hypertension, and non-alcoholic fatty liver disease [7,8]. At present, numerous modulators of TRP channels have been documented to exert significant roles in the pathogenesis of metabolic diseases (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…), acid (H + ) and other biochemical factors (10). They also have an efferent function through local release of mediators such as neuropeptides (substance P [sP] and calcitonin gene related peptide [CGRP]) (11). TRPV1 + neurons are of known importance in pro-inflammatory reactions (12) and islet infiltrating lymphocytes express receptors for neuropeptides (13).…”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 + neurons are of known importance in pro-inflammatory reactions (12) and islet infiltrating lymphocytes express receptors for neuropeptides (13). In this regard, it has been previously reported that NOD mice have a functional defect in sensory cells, particularly in those which express the TRPV1 receptor (11). Mutations in TRPV1 have also been related with T1D in humans (14).…”
Section: Introductionmentioning
confidence: 99%